Customer complaining behaviour and its consequences in the credit card industry: an empirical investigation in the developing Indian economy. (2015) - Pandey, Shivendra Kumar
Understanding complaining behaviour in Indian credit card industry was the objective of this research. A foreign bank operating in India had collected customer complaint data in a natural environment and data on 957 such customers were provided by the bank. The antecedents of the complaint process were objectively measured with variables such as the number of times contacted and time taken for resolution of the complaint. The analysis revealed that customers are willing to wait a bit more for a resolution of the complaint provided they are not required to do follow ups. The bank's service quality mediates between the satisfaction from the complaint process and recommendation to a friend. Implications for managers and researchers are discussed.